ANALISIS DAN PERANCANGAN SITUS WEB PENJUALAN PADA PT. BINA BARATHA MANGGALA - Akhmad Budi (Jurnal Informatika dan Bisnis, 2012)
At the present time, technology is growing by leaps and bounds. Many people who keep abreast of technological developments, one of them is the internet. One of the business or enterprise that uses the internet to support its performance is e-commerce. Many benefits of using the web in trade, such as for marketing and sales. PT Bina Baratha Manggala is a company engaged in the lubricants industry. In the process of business, marketing is done manually by a direct marketing meeting and introduced the company's products to prospective customers. In the sales process, customers purchase products by contacting the company. The purpose of this research is to design a website to expand marketing and make the sales process on-line. This website was designed based on the golden rule in designing the user interface, and is written in PHP easy HTML using Macromedia Dreamweaver 8. The design of this website also uses MySQL database to design normalized tables, and XAMPP to connection to the database server. The collection of user requirements and other informations was done by interviewing staff and the owner of PT Bina Baratha Manggala. Designed system is illustrated with a data flow diagram and entity relationship diagrams. A data dictionary is used as a source of data for the process of normalization, resulting the tables in the database. This website provides not only information to visitors about PT Bina Baratha Manggala and products provided, but also on-line sales features. Sales processes will be done through payment confirmation either from member or administrator.Â  The conclusion of research is, that this website can help business processes inÂ  PT Bina Baratha Manggala sales process on-line and also in managing the sales data, and provide useful information in the resulting reports that is useful to the owner.